COMPORTAMENTO DE PASTEJO, CONSUMO DE FORRAGEM E DESEMPENHO DE BOVINOS EM SISTEMAS SILVIPASTORIS COMPOSTOS POR BABAÇU E MONOCULTURA DE CAPIM MARANDU - ARAÚJO, Ricardo Alves de (2015)
This work aimed to evaluate the animal performance, forage intake, behavior of grazing and the spatial distribution of bovine feces of growth, kept in silvopastoral systems formed by babassu and HAL. The experiment was carried out on the Farm Living Water, in the municipality of de Matinha-MA, region of Baixada Maranhense, in the period of April to October 2013.The treatments used were: monoculture Marandu palisadegrass and three densities of palm trees of babassu more Marandu palisadegrass (SSP), being: 0, 80, 131, 160 adult palms/ha, characterizing monoculture (Mono), low density of palm trees (BDP), average density of palm trees (MDP) and high density of palm trees (ADP), totaling four treatments. These were imposed on experimental units in a randomized design with arrangement in a split-plot, with the plots the periods rainy and dry seasons, already in the subplots densities of palm trees. The system used was the continuous manning, with five crossbred cattle Nelore x Guzera per experimental unit. Over time, steers were placed and removed from each paddock, according to need. The composition of the grass was equal in all pastoralist systems and there was no difference between the two periods, probably because of the extension of the PC. In relation to the consumption for the two periods difference was observed only in Mono and MDP (P>0.05), already among the systems there was no difference. he consumption of MS was between (2.6% LW) for the PC and (2.8 % LW) for the PS, and that these values are very close the tables of requirements of the National Research Council, which is (2.7 %LW) for animals in that category. The consumption values for the gains of weights obtained in the two periods are above the expected values.The rate of recovery of chromium in the feces for treatments Mono, BDP, MDP and ADP in PC was 92.35; 91,32; 90.78 and 91,00 %, with an average recovery of 91.36 %, already for the PS was 92,32 %. There was no significant difference for both periods as for densities. We observed a higher ADG in animals kept in pastures with BDP. The gain per area (GP, kg.ha-1) was also greater in BDP , getting around 84,37kg.ha-1.Animals kept in silvopastoral systems present a better gain in relation to maintained in Mono, being that the system of BD provided better daily weight gain of animals. On the PC the largest grazing time was observed in the animals of MDP and PS monoculture, already the time of rumination was greater in BDP and lowest in MDP during the PC, already in the dry season the monoculture.Activities such as drinking water and consume the mineral salt was greater in ADP and in monoculture for the PC and PS respectively. During the PC it was observed by the index of dispersion standardized that the distribution of plaques of feces within the paddocks was in aggregate form, except for the ADP that occurred in a uniform way. Already in PS MDP and ADP showed a distribution in a uniform way, the others were in aggregate form.It was observed that the behavior of grazing was influenced by sward structure mainly in SSP's due to shading provided by babaçuais. The silvopastoral systems formed by palm trees of babassu and palisadegrass can be used as a means to improve animal production and forage.